12(S)‐hydroxyeicosatetraenoic acid is significantly increased in diabetic kidney disease and associated with renal function decline. Issue 6 (17th June 2022) - Xu, Jie; Jin, Li; Sun, Yi; Zhang, Rong; Chen, Xianghui; Zhou, Ranran; Gu, Yunjuan; Hu, Cheng
Abstract: Aims: 12(S)‐hydroxyeicosatetraenoic (12(S)‐HETE), an alternate arachidonic acid metabolite, has been recently examined in metabolic disease. However, the role of 12(S)‐HETE in diabetic kidney disease (DKD) remains unclear. We studied for the first time the relationship of serum 12(S)‐HETE and DKD and renal function parameters in a Chinese population. Materials and Methods: We recruited 275 subjects who were diagnosed with type 2 diabetes (T2DM) for more than 10 years, including 149 DKD patients and 126 T2DM patients without DKD. Serum 12(S)‐HETE was measured using the enzyme‐linked immunosorbent assay. Results: Serum 12(S)‐HETE was significantly higher in DKD patients than controls [384.69 (77.54, 1003.05) pg/ml and 17.77 (8.11, 75.13) pg/ml, respectively, p  < 0.0001]. Compared to controls, 12(S)‐HETE was significantly increased in both macroalbuminuria and microalbuminuria groups ( p  < 0.0001). Further, the macroalbuminuria group also had a higher serum 12(S)‐HETE level compared to the microalbuminuria group ( p  = 0.0063). Moreover, serum 12(S)‐HETE was positively correlated with the albuminuria level ( r  = 0.5833, p  < 0.0001), serum creatinine ( r  = 0.2725, p  < 0.0001), and was negatively associated with the estimated glomerular filtration rate ( r  = −0.2085, p  = 0.0005). Further, receiver operating characteristic analysis (ROC) revealed that 12(S)‐HETE had a good performance of distinguishing DKD from controls (AUC 0.828) with a sensitivity of 0.913 and a specificity of 0.711. Conclusion: Our findings revealed that serum 12(S)‐HETE significantly associated with DKD and disease severity, suggesting that serum 12(S)‐HETE may be used as a potential biomarker for the early diagnosis of DKD.